MCMI-III Profiles of Convicted Contact Sexual Offenders: A Cluster Analysis. Issue 5 (20th October 2019) - Soldino, Virginia; Carbonell-Vayá, Enrique J.; Perkins, Derek; Tibau, Xavier-Andoni
ABSTRACT: As suggested by previous research, the study of personality traits among sexual offenders could be an important consideration in the understanding of sexual offending. This study aims to explore the possibility of classifying sexual offenders according to their personality profiles. Based on the MCMI-III scores of 97 convicted contact sexual offenders, a cluster hierarchical analysis was performed. Next, the groups were characterized according to their sociodemographic and criminological variables and significant differences between them were sought. The two clusters found did not show different MCMI-III prototypical personality profiles, and both groups only varied in the degree of general psychopathology. The results suggest the existence of two personality profiles labeled as "pathological" and "adapted/non-pathological". The usefulness of the MCMI-III in the evaluation of sexual offenders seems limited to the detection of the presence or absence of general psychopathological symptoms. Implications of these findings for interventions are discussed.